Following the enzymatic digestion of chondroitin sulfate by a simple GPC analysis - Silva, C. (2015)
We describe the use of gel permeation chromatography (GPC) setup with four size exclusion columns for analysis of enzymatically digested glycosaminoglycans (GAGs). This setup provides information about the molecular weight (Mw) and concentration of all species (low and high Mw) present in the digests in a single measurement. The data about the fraction with high Mw (often omitted in the analysis of GAG digests) provide direct evidence about the mechanisms of action of the enzymes. We proved the feasibility of this methodology by applying it to chondroitin sulfate (CS) substrates with different molecular weight and sulfation pattern and using different enzymes (hyaluronidase and chondroitinase). NMR analysis of the obtained digests fractionated by ultrafiltration confirmed the results obtained by GPC setup and reveal further details about the degradation mechanisms: (i) both enzymes preferentially attack 4-sulfated chondroitin and (ii) additionally to the well documented endolytic activity of hyaluronidase we also observed a low lyase activity for this enzyme reflected in the detected minor exolytic breakage. Finally, we demonstrate that CS with medium molecular weight (12â 60 kDa) which is sulfated mainly at 6-position can be obtained in good yields by enzymatic digestion and following ultrafiltration.